Almrah Syrian Image In The Drma Of The Syrian Tv - Zrika, Yusra (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The purpose of this Aldrashala identify the image Alnmtihalta Tardhadaramavi Syrian television and be Aldrashmn community group of serials Aldramahalsorahastkhaddmt Albageshmenhj content analysis to identify the stereotype offered by those soap operas and disclosure of background form a mirror image in a TV drama and the circumstances that contributed to the pull that image in a way that a certain order to ascertain health or wrong hypotheses that will put them and after analysis of the data shows that were stained traditional stereotype for the bulk of the dramas of the Syrian and confined women in the triangular corner of the female parent wife wear it Our lady of the kitchen and interested bellies family-sided interested offers fashion on the other hand، a woman that fail to be typical wife in case went to work and participate in building the Alizma.